The Definitive Guide to MySQL5 - Kofler, Michael; SpringerLink (Online service) (Berkeley, CA : Apress, 2005)
MySQL 5 is slated to be the most significant release in the products history. The Definitive Guide to MySQL 5, Third Edition is the newest revision of Michael Koflers popular book. This is the first book to offer in-depth instruction about the new features of the world's most popular open source database server. Updated to reflect changes in MySQL version 5, this book will expose you to MySQL's impressive array of new features: views, stored procedures, triggers, and spatial data types. Whether you're a novice or intermediate user, you will benefit from extensive coverage of core MySQL features like user administration, basic and advanced querying, and security. You will also be introduced to several standard and third-party tools, like MySQL Administrator, Query Browser, and the popular PHPMyAdmin tool.
What Is MySQL? -- The Test Environment -- Introductory Example (An Opinion Poll with PHP) -- Administrative Tools and User Interfaces -- mysql, mysqladmin, and mysqldump -- MySQL Administrator and MySQL Query Browser -- phpMyAdmin -- Microsoft Office, OpenOffice/StarOffice -- Fundamentals -- Database Design -- An Introduction to SQL -- SQL Recipes -- Access Administration and Security -- GIS Functions -- Stored Procedures and Triggers -- Administration and Server Configuration -- Programming -- PHP -- Perl -- Java (JDBC and Connector/J) -- C -- Visual Basic 6/VBA -- Visual Basic .NET and C# -- Reference -- SQL Reference -- MySQL Tools and Options -- API Reference.
Keywords: Computer science; Software engineering; Computer Science; Software Engineering/Programming and Operating Systems; Electronic books